Three-dimensional Au nanoparticles-decorated γ-Fe2O3@reduced graphene oxide core-shell heterojunctions for highly sensitive room-temperature gas sensors. Issue 24 (15th December 2022) - Zou, Cheng; Ma, Defu; Su, Yanjie; Zhu, Mingkui; Zhou, Bo; Shao, Feng; Hu, Nantao; Yang, Zhi; Xie, Haijiao; Zhang, Yafei
Abstract: Au nanoparticles (Au NPs)-decorated three-dimensional (3D) reduced graphene oxide (RGO)-wrapped γ-Fe2 O3 nanospheres (γ-Fe2 O3 @RGO) heterojunctions have been synthesized via a combination of self-assembly and in-suit ultrasound-induced decoration method. The Au NPs-decorated γ-Fe2 O3 @RGO (γ-Fe2 O3 @RGO-Au) heterojunctions sensor exhibits an excellent response of 384% to 50 ppm NO2 at room temperature, which is enhanced compared to the sensors based on bare RGO (35%) and γ-Fe2 O3 @RGO (243%). Furthermore, the calculation based on density functional theory (DFT) has been used to simulate the interaction between NO2 gas and sensing materials, thereby providing a theoretical basis for our experimental results. Moreover, the enhanced gas-sensing properties of γ-Fe2 O3 @RGO-Au have been explained by combing the 3D structure, the as-formed heterojunctions with chemical and electronic effect of Au NPs. Our results demonstrate an effective strategy for designing high performance RGO-based sensors based on 3D core-shell heterojunctions.